CONSUMERS INTEREST FOR ERGONOMIC KNOCK-DOWN WATER FILTERS - Santoso, Gempur; Wiyarno, Yoso; Poniman (Tibuana, 2019)
Provision of clean water is still a problem currently in Indonesia , 80% of the population still consume water that does not meet health standards. Is the ergonomic knock down water filters to provide clean water become consumer interest?. The study was designed using a comparative descriptive study, The number of respondents is 30 people who use water filters. Data is taken by observation and questionnaire. Data is analyzed using descriptive percentages. The result of the research shows that the "C" (Portable Water Filter Purifier) Water Filter form is the most consumers interest (40%), "B" water filter form (Indoor Drinking Water Filter Stainless Steel Water Purifier) is (36.6%), and the least interested is form of "A" (Mi Water Purifier) water filter (23.3%).73.3% of respondents choose stainless steel material. Conclusion: water filter users have the highest interest in the type of portable knock down filter made of stainless steel material, easily installed and used ergonomically, and the material is not easily corrosion.